2022
DOI: 10.3390/foods12010001
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes and Acceptability of Wheat Pancakes with the Addition of Edible Insects: Mealworm (Tenebrio molitor), Buffalo Worm (Alphitobius diaperinus), and Cricket (Acheta domesticus)

Abstract: The aim of this study was to determine the degree of acceptability of wheat pancakes with the addition of 10%, 20%, and 30% meal from three edible insect species (Alphitobius diaperinus, Tenebrio molitor, Acheta domesticus, respectively). Both consumer attitudes and the acceptability of the test samples were analysed. The study results show that the amount of additive had a statistically significant effect on all of the organoleptic evaluation’s distinguishing features, while the type of additive did not have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Kostecka et al (2017) also reported that approximately 37% of participants in Poland found products with processed insects, such as insect flour, to be acceptable for introduction in the market (Kostecka et al, 2017). Based on the study by Mazurek et al (2022), consumer acceptability can be significantly influenced by the form of the insects, specifically their flavour, and the way in which they were presented. The studies used lesser mealworm powder as a flavour in preparing wheat pancakes.…”
Section: Sociodemographic Circumstancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kostecka et al (2017) also reported that approximately 37% of participants in Poland found products with processed insects, such as insect flour, to be acceptable for introduction in the market (Kostecka et al, 2017). Based on the study by Mazurek et al (2022), consumer acceptability can be significantly influenced by the form of the insects, specifically their flavour, and the way in which they were presented. The studies used lesser mealworm powder as a flavour in preparing wheat pancakes.…”
Section: Sociodemographic Circumstancesmentioning
confidence: 99%
“…Hence, it can be said that not all consumers in European countries are ready for insect-based food, and additional factors need to be considered before commercialization. Factors such as food disgust, neophobia, and seeking sensation have been identified as predictors of the acceptance of edible insects, and these factors will be discussed further in the product section (Mazurek et al, 2022).…”
Section: Sociodemographic Circumstancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consuming insects has the potential to alleviate animal suffering in comparison to the consumption of conventional livestock. In addition to the aforementioned environmental advantages, insects possess significant nutritional value, as they are notably abundant in high-quality protein that consist of crucial amino acids, such as tryptophan lysine, tryptophan, and threonine [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts undertaken so far in this respect should be deemed insufficient; therefore, there is a need to continue and expand research in this field. Many innovative projects and concepts related to the development of insect-based food products, including muffins, pa ˆte ´s, corn extrudates, pancakes, sponge cake, and bars [23,69,[77][78][79][80][81], have been elaborated, and their results are being implemented across Poland. Nevertheless, there is a cognitive gap in the Polish and central and eastern European scientific literature in this field.…”
Section: Introductionmentioning
confidence: 99%